Creating a new index to evaluate imbalance in medical demand and supply when disasters occur. Issue 4 (15th July 2018) - Takahashi, Kohei; Morimura, Naoto; Takeuchi, Ichiro; Abe, Takeru; Toida, Chiaki; Hattori, Jun; Hattori, Kyoko; Honda, Hideki; Uchiyama, Munehito; Matsuda, Kiyoshi; Nakagawa, Yoshihide; Asari, Yasushi
Abstract : Aim: This study examines the use of the medical risk/resource ratio (RRR) and need for medical resources (NMR) as new indicators of the imbalance in medical demand and supply in disasters. These indicators are used to quantify the medical demand–supply imbalance per disaster base hospital, examine the demand–supply imbalance in the region, and verify the need for medical support. Methods: We calculated the RRR of each disaster base hospital by dividing the revised estimate of the number of patients with the number of empty beds. We calculated the required number of hospital beds as the NMR to restore the RRR of each disaster base hospital to two. The RRR and NMR were combined, and prioritization for medical support was classified into three levels. Results: The median RRR was 23 (range, 1–101), and the median NMR was 943 (range, 0–2, 124). Fifteen hospitals had a medical support priority of 1, five hospitals had a priority of 2, and 13 hospitals had a priority of 3. Conclusion: The medical demand–supply imbalance and amount of medical support needed can be quantified using RRR and NMR, which allows examination of the priority level for medical support. Abstract : This study examines the use of the medical risk/resource ratio (RRR) and need for medical resources (NMR) as new indicators of the imbalance in medical demand and supply in a disaster. The medical demand–supply imbalance and amount of medical support needed can be quantified using RRR and NMR.